Discrete-Trap Effects on 3-D NAND Variability – Part II: Random Telegraph Noise - Gerardo Malavena; Salvatore M. Amoroso; Andrew R. Brown; Plamen Asenov; Xi-Wei Lin; Victor Moroz; Mattia Giulianini; David Refaldi; Christian Monzio Compagnoni; Alessandro S. Spinelli (IEEE Journal of the Electron Devices Society)
In Part II of this article we discuss the impact of a discrete treatment of traps on 3-D NAND Flash random telegraph noise (RTN). A higher RTN results when discrete traps are taken into account, that can only be explained by a stronger influence of the discrete charged traps on the current conduction, leading to more percolation. The effects are then investigated as a function of the cell parameters, showing that a continuous model for traps cannot reproduce the correct dependence.